Peningkatan Pemahaman Konsep Lembaga Pemerintahan Desa Melalui Model Pembelajaran Kooperatif Tipe Make A Match pada Peserta Didik Sekolah Dasa - A G Prihagnolo, H Mahfud, Karsono (Jurnal Pendidikan Dasar, 2019)
The purpose of this study was to improve the understanding of the concept of Village Government Institutions through the application of the Cooperative Learning Type Make A Match model to Grade IV Students of SD Negeri 02 Tugu Jumantono in the Academic Year 2017/2018. This research is in the form of Classroom Action Research (CAR) conducted in two cycles, each cycle consisting of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and fourth grade students of SD Negeri 02 Tugu Jumantono, totaling 21 students, consisting of 10 female students and 11 male students. Data collection techniques used are tests, observations, interviews, and documents. The data analysis technique used is an interactive analysis technique consisting of three components, namely data reduction, data presentation, and conclusion drawing. The conclusion of this research is that the application of the Cooperative Learning Type Make A Match model can improve the understanding of the concept of Village Government Institutions in fourth grade students of SD Negeri 02 Tugu Jumantono in the 2017/2018 Academic Year. Keywords: concept understanding, Village Government Institution, Cooperative Make A Match Type